Learning mechanism used in strengthening local automotive vendor's absorptive capacity - Musa, Suria; Othman, Siti Norezam; Hami, Norsiah; Mustafar, Mastora (2010)
in attaining competitive advantage, inevitably, firms had to innovate. The development of innovation capability was crucial for firms to stay in competition.In developing firm innovation capability, absorptive capacity and learning mechanism were important factors.Absorptive capacity is built through accumulation of prior knowledge base and internalization of the knowledge in an organization. The purpose of the study was to describe learning approch used by firms in strengthening local automotive vendor's absorptive capacity.This paper also explored one component of absorptive capacity named firm's knowledge base,The research design used in this descriptive study was quantitative method with questionnaires mailed to the respondents. The sampling technique for this study was random sampling with a sample size of 113 automotive component manufacturers,who supplied automotive parts to various car assemblers and manufacturers.Out of 113 automotive manufacturers,only 45 respondents responded to the survey sent to them.The results of the study indicated the level of manufacturers' absorptive capacities was high in the project management,product development performance measurement,cost benefit analysis and early production output evaluation areas.In addition,the learning mechanism adopted by most of the manufacturers were interacting among employees in the R&D or engineering department as a means for them of solve problem related to product development design and acquiring knowledge in PDD through documenting explicit knowledge in a manual or product catalogue.The implication of this study was the manufacturer needed to improve their knowledge absorption capacities through proposed learning mechanisms.